Implikasi Keterampilan Berpikir Kritis Terhadap Pencapaian Organisasi - As’adi Khas; Mochammad Isa Anshori (Universitas Veteran Bangun Nusantara, 2023)
This research aims to investigate the impact of critical thinking skills on organizational performance through a systematic review method. The results of this study indicate that critical thinking skills have a significant impact on various aspects of organizational achievement, including individual performance, innovation and problem-solving, decision-making, communication, and organizational planning. Employees with critical thinking skills tend to have better performance, are able to generate innovation, make more rational decisions, and contribute to effective communication and collaboration. Additionally, critical thinking skills also influence organizational planning and organization, thereby promoting critical thinking in maximizing organizational goals. This research serves as a reference for managers and business practitioners in designing effective strategies to enhance work quality, innovation, good decision-making, as well as effective communication and collaboration within the organization through the development of employees' critical thinking skills.